The Auhtority of the Audit Board of The Republic Of Indonesia in Carrying Out Audits of Village Financial Management (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to determine the authority of the Audit Board of The Republic of Indonesia in carrying out audits of Village Financial Management. This research is a normative legal research with a statutory approach and conceptual approach. Based on the research results it is known that the inspection conducted by the Audit Board of The Republic of Indonesia covers all elements of state finance as stipulated in Law Number 17 of 2003, but village finance is not explicitly mentioned in the regulation. Referring to the approach used in formulating State Finances in a general explanation of Law Number 17 of 2003 concerning State Finances, can be said that finance managed by the village government is also included in the scope of state/regional finances which are also the object of Supreme Audit Board audit. This is related to the clarity of the status and legal certainty over villages in the constitution of the Republic of Indonesia. Village government as the lowest body of authority has the original authority to regulate its own household also has the authority and power as a gradual delegation of government over it ie the regional government and the central government, so that the central/regional government and village government is an inseparable part of government administration country. Therefore village finance is a state/regional financial subsystem as a consequence of the division of tasks among the government, regional government and village government.